2007
DOI: 10.1128/jvi.02714-06
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Restrictions of Human Immunodeficiency Virus Type 1 in Feline Cells

Abstract: The productive replication of human immunodeficiency virus type 1 (HIV-1) occurs exclusively in defined cells of human or chimpanzee origin, explaining why heterologous animal models for HIV replication, pathogenesis, vaccination, and therapy are not available. This lack of an animal model for HIV-1 studies prompted us to examine the susceptibility of feline cells in order to evaluate the cat (Felis catus) as an animal model for studying HIV-1. Here, we report that feline cell lines harbor multiple restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
54
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 89 publications
5
54
1
Order By: Relevance
“…The discovery of the cellular antiviral cytidine deaminase A3G in search for the Vif cofactor explained many in vitro observations regarding the replication of HIV-1 and HIV-1 ⌬vif in specific human cells (5,49,78,91,100). It also contributed to explain the narrow host range of HIV-1 that shows spreading replication only in humans and chimpanzees (49,59). Such defined interactions of Vif proteins with cognate A3 proteins had been shown so far only for HIV, SIV, and Feline immunodeficiency virus (49,58,74).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the cellular antiviral cytidine deaminase A3G in search for the Vif cofactor explained many in vitro observations regarding the replication of HIV-1 and HIV-1 ⌬vif in specific human cells (5,49,78,91,100). It also contributed to explain the narrow host range of HIV-1 that shows spreading replication only in humans and chimpanzees (49,59). Such defined interactions of Vif proteins with cognate A3 proteins had been shown so far only for HIV, SIV, and Feline immunodeficiency virus (49,58,74).…”
Section: Discussionmentioning
confidence: 99%
“…Three closely related feline A3C (fA3C) proteins (fA3Ca, fA3Cb, and fA3Cc) are active against feline foamy virus but not vif-deficient FIV (60). In contrast, the two other proteins (fA3H and fA3CH) have antilentiviral effects, as they restrict ⌬vif FIV and HIV-1 with vif intact (60,61). fA3CH, the only two-domain feline A3 protein, is an unusual hybrid encoded by exons 1 to 3 of fA3Ca, exon 4 of fA3Cb, and exons 2 to 5 of fA3H (60).…”
mentioning
confidence: 99%
“…Murine T cells also display a postentry block to HIV-1 (3). Even if all necessary human dependency factors can be identified and made to function in a nonprimate animal with transgenic methods, HIV-1 replication is inhibited in the cells of many primate (29,74,87) and nonprimate (32,50,61,76,84) species by the antiviral activity of species-specific restriction factors, such as TRIM5␣, TRIMCyp, and APOBEC3 (A3) proteins. The APOBEC3 proteins are DNA and RNA cytidine deaminases, some of which have antiviral activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of other mammalian species has shown that the mouse genome contains a single APOBEC3 gene (the mA3 gene), while cats express at least three distinct APOBEC3 proteins (11,37). While nonmammalian vertebrates, such as birds and fish, do not carry any genes encoding any APOBEC3 proteins, all vertebrates do carry genes encoding activation-induced deaminase (AID), a DNA-editing enzyme that plays a role in the diversification of antibody genes (11).…”
mentioning
confidence: 99%